I suspect this is what you mean, if let me know
2x(3)^2+x(2)^2
2(3)(9)+3(4)
54+12=66
Answer:
3rd Answer =Option A is the Correct Answer
Step-by-step explanation:
Answer:
<h2>f(x - k) = (x - k)²⇒ k = 5</h2>
Step-by-step explanation:
f(x) + n - shift the graph n units up
f(x) - n - shift the graph n units down
f(x - n) - shift the graph n units to the right
f(x + n) - shift the graph n units to the left
==============================================
Look at the picture.
The graph has been shifted 5 units to the right.
Therefore we have f(x - 5).
Answer: Half of a apple pie
Step-by-step explanation:
1/2 is half
The measures of the angles in a triangle add up to 180°.